Pengukuran hasil pembelajaran kursus dari persepsi pelajar di Jabatan Kejuruteraan Mekanikal, Universiti Industri Selangor - Khairul Anuar Mohd Ali; Mohammad Alinor Abdul Kadir; Amirruddin Abdul Kadir (Penerbit ukm, 2007)

(untitled)
A good learning program is essential in achieving high quality education. The learning program proposed in this study is based on the assumption that different learning environment and objective require different learning method. Outcome Based-Education (OBE) determine the design, construction, communication and, teaching documentation which are in line with the defined outcomes to enhance and maintain the learning quality. The teaching in OBE needs clear, observable demonstrations of student learning in defining the student needs of achieving success, identifying and designing strategies for the students to achieve. Study is made on six courses chosen from the Mechanical Engineering Program, UNISEL for Semester July session 2005/2006. The study proved that the learning structure supported by OBE can set a good class practice in achieving the defined outcomes